Meticillin-susceptible Staphylococcus aureus transmission among healthcare workers, patients and the environment in a large acute hospital under non-outbreak conditions investigated using whole-genome sequencing - Coleman, David; Kinnevey, Peter (My University, 2022)
Background: The role of meticillin-susceptible Staphylococcus aureus (MSSA) colonization of healthcare workers (HCWs), patients and the hospital environment in MSSA transmission events (TEs) is poorly understood. Aims: The role of meticillin-resistant Staphylococcus aureus (MRSA) was investigated recently under non-outbreak conditions in a large hospital with a history of endemic MRSA over 2 years using whole-genome sequencing (WGS). Numerous potential MRSA TEs were identified. The present study investigated MSSA TEs from the same sources during the same 2-year hospital study. Methods: HCW (N=326) and patient (N=388) volunteers on nine wards were tested for nasal and oral MSSA colonization over 2 years. Near-patient environment (N=1164), high-frequency touch sites (N=810) and air (N=445) samples were screened for MSSA. Representative MSSA and clinical isolates were sequenced and analysed by core genome multi-locus sequence typing. Closely related isolates (≤24 allelic differences) were segregated into related isolate groups (RIGs). Potential TEs involving MSSA in RIGs from HCWs, patients and patient infections were identified in combination with epidemiological data. Findings: In total, 635 MSSA were recovered: clinical isolates (N=82), HCWs (N=170), patients (N=120), and environmental isolates (N=263). Twenty-four clonal complexes (CCs) were identified among 406/635 MSSA sequenced, of which 183/406 segregated into 59 RIGs. Numerous potential HCW-to-patient, HCW-to-HCW and patient-to-patient TEs were identified, predominantly among CC5-MSSA, CC30-MSSA and CC45-MSSA. HCW, patient, clinical and environmental isolates were identified in 33, 24, six and 32 RIGs, respectively, with 19/32 of these containing MSSA related to HCW and/or patient isolates. Conclusions: WGS detected numerous potential hospital MSSA TEs involving HCWs, patients and environmental contamination under non-outbreak conditions.
Transmission of MSSA under non-outbreak conditions
Keywords: Whole-genome sequencing; Oral colonization; Non-outbreak conditions; Meticillin-susceptible Staphylococcus aureus; Nasal colonization; Environmental contamination; Hospital transmission; MSSA; MSSA colonization; Genes & Society; Immunology, Inflammation & Infection; Hospital transmission events; Methicillin-susceptible Staphylococcus aureus; Oral carriage of Staphylococcus aureus; whole-genome sequencing; Health